2011
DOI: 10.1002/bit.24367
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of instability of chinese hamster ovary cell lines expressing recombinant antibodies and antibody‐fusion proteins

Abstract: One of the most important criteria for the successful manufacture of a therapeutic protein (e.g., an antibody) is to develop a mammalian cell line that maintains stability of production. Problems with process yield, lack of effective use of costly resources, and a possible delay in obtaining regulatory approval of the product may ensue otherwise. Therefore the stability of expression in a number of Chinese hamster ovary (CHO) derived production cell lines that were isolated using the glutamine synthetase (GS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 50 publications
3
92
0
Order By: Relevance
“…Older generation cells had an altered metabolism together with an elevated level of the transcription factor GADD153 mRNA, indicative of increased cellular and specifically ER stress (Bailey et al 2012). Related to these observations, Dorai et al (2012) observed that unstable CHO clones were more prone to apoptosis, indicated by higher levels of the apoptotic markers annexin V and caspase 3.…”
Section: Impact Of Long-term Sub-culture On Cell Populationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Older generation cells had an altered metabolism together with an elevated level of the transcription factor GADD153 mRNA, indicative of increased cellular and specifically ER stress (Bailey et al 2012). Related to these observations, Dorai et al (2012) observed that unstable CHO clones were more prone to apoptosis, indicated by higher levels of the apoptotic markers annexin V and caspase 3.…”
Section: Impact Of Long-term Sub-culture On Cell Populationsmentioning
confidence: 86%
“…This threshold level is thought to be the point at which the downstream biosynthetic reactions utilising recombinant mRNAs are saturated, and therefore only when the transcript copy number declines further will there be any phenotypic consequence. Cell line instability can be observed both in the presence and absence of selective pressure, although it may be both more likely and more precipitous once the selective pressure has been removed (Dorai et al 2012;Kim et al 2011;Osterlehner et al 2011;Yang et al 2010;Chusainow et al 2009). Where a decline in recombinant Mab mRNA has been observed, it can affect both the HC and LC genes in cell lines created using both DHFR and GS expression systems, as well as in low and high productivity clones (Kim et al 2011;Yang et al 2010;Chusainow et al 2009).…”
Section: Epigenetics and Cell Line Instabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…In order to reduce cost and time in biopharmaceutical development, emphasis is on scale-down models and predictive technologies. However, the shake-flask culture, which is the widely used scale-down model of fedbatch bioreactor, does not mimic the environmental conditions of a stirred-tank, fed-batch bioreactor well [16,39]. Consequently, in our laboratory, the final step in the cell line screening process is routinely carried out in bioreactors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, robust and highly productive host cell lines can be deployed by increasing the efficiency of gene expression that regulates proliferation [11] survival and longevity [12][13][14]. Finally, methods that allow early prediction of unstable and stable cell lines by measuring intra-cellular Ab content for example, by flow cytometry [15,16] are highly desirable.…”
Section: Introductionmentioning
confidence: 99%